Molecular Mechanisms of Low-Temperature Stress Response in the Muscle of Yellowtail Kingfish (Seriola aureovittata) - Yushun Tian; Ruonan Zhang; Bingxin Wu; Mingxin Ji; Xinyang Li; Xinyu Cao; Chen Jiang (Fishes, 2025)
The yellowtail kingfish (Seriola aureovittata), a commercially important marine species, encounters significant survival challenges under low-temperature conditions during winter aquaculture. To elucidate its molecular adaptation mechanisms, this study employed RNA-Seq to analyze transcriptional responses in juvenile muscle tissues under acute cold stress (10 °C) at 0, 6, 12, and 24 h. Differential gene expression analysis revealed time-dependent patterns, with 269, 863, and 984 differentially expressed genes (DEGs) identified at 6, 12, and 24 h, respectively. Key pathways were identified, including lipid metabolism, carbohydrate metabolism, and stress response. Sestrin3 upregulation implicated AMPK-mediated energy homeostasis in cold adaptation. These findings provide novel insights into the molecular strategies underlying cold adaptation in yellowtail kingfish, offering potential targets for breeding cold-resistant strains and improving aquaculture resilience.